The Relationship between Self Control and Job Stress with Police Aggressiveness - Andra Purnama Putra; Rr. Amanda Pasca Rini; Sahat Saragih (Universitas Muhammadiyah Sidoarjo, 2017)
Aggression is a behavior that is intentionally to hurt,threaten, or endanger others or another object physically or verbal and direct or indirect. Aggression is a common characteristic that can’t be erase from human life, especially police. All police has it own aggression, but the capacity is different with others police depend on self control and work stress they have. The research purpose’s to know correlation of self control (X1) and work stress (X2) with police aggression (Y). It subject is sergeant policeman in Sidoarjo. Subject amount 120 Police. The sampel taken by purposive sampling method. Statistical analysis method that be used is regression and using SPSS 22.00 for windows. the first result is there is correlation between self control, work stress and Police aggression.the second result is there is correlation negatively between self control and aggression. The third result is there is correlation positively between work stress and aggression.